EVALUATION OF ARCHITECTURAL COMPONENTS IN BAYUNG GEDE VILLAGE SETTLEMENT, BALI AS A TOURISM OF SPECIAL INTEREST - Vianthi, Ni Putu Yunita Laura; Putra, I Dewa Gede Agung Diasana (ASTONJADRO, 2022)
Special interest tourism is one of the efforts to provide alternative tourist attractions and sustainable tourism development in Bali. Visits of both domestic and foreign tourists to Bali in the last 4 years (2015-2019) have increased by an average of 8%. Now the tourism sector in Bali, especially in Bangli Regency, is starting to investigate or explore the possible development of tourist attractions through the development of tourist villages. In this case, the development of special tourism, including the tourist village of Bayung Gede, Bangli is very dependent on the architectural components of traditional settlements and the traditions of the residents in it as a source of attraction and main attraction for tourists. However, the influence of tourism has led to the transformation of traditional settlements. In this case, the transformation has given rise to a paradoxical phenomenon where on the one hand traditional housing attracts tourists, on the other hand the presence of tourists has led to a transformation of the traditional settlements of an area. The purpose of this study is to examine the architectural components of the Bayung Gede Village settlement as a tourism potential based on special interest tourism and then to find out how far the tourism architectural potential is found and how strong the Bayung Gede Village settlement icon is as a special interest DTW. The method used is a qualitative-exploratory and descriptive method. The results show that the traditional settlement of Bayung Gede Village contains elements of special interest tourism such as elements of novelty seeking, quality seeking, enriching, rewarding, adventuring and learning, so that it has the potential as religious tourism (the existence of four types of graves), culture (settlement and residential layout) and citrus plantation sector agro-tourism in improving the economic sector of the community. Investigation and inventory of Bayung Gede traditional housing is an effort to find a village icon that has prestige that can attract tourists to visit and be able to compete with other tourist villages.